Developing mathematics teaching materials using maritime context for higher-order thinking in junior high school - Malalina; Putri, Ratu Ilma Indra; Zulkardi; Hartono, Yusuf (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Mathematics learning using high-order thinking skills is crucial for students. High-order thinking skills can be developed through learning materials with contexts relevant to the student's environment. This research aims to: produce maritime context mathematics teaching materials for higher-order thinking in Junior High Schools that are valid, practical, and have a potential effect on analytical and evaluation skills. The subjects of this study were 7th-grade students at SMP Tamansiswa Palembang, SMP Tamansiswa Mariana, and SMP Tamansiswa Sungai Buah. Data collection techniques include walkthroughs, interviews, observations, documentation, and tests. Data analysis is conducted qualitatively through descriptive methods. The research development of maritime context mathematics teaching materials for higher-order thinking at Junior High Schools has been validated based on content, construct, and language by expert reviews. During one-to-one interactions, students demonstrated their comprehension of the teaching materials and their ability to analyze and evaluate the student worksheets (SW) and questions. Practicality was observed during small group interactions, as students encountered no difficulties in solving problems on the SW and questions using analytical and evaluative skills. Furthermore, the field test demonstrated that the maritime context mathematics teaching materials have the potential to enhance students' analytical and evaluative abilities. In conclusion, this research has produced valid, practical, and potentially effective maritime context mathematics teaching materials for higher-order thinking at Junior High Schools, which can enhance students' analytical and evaluative abilities.